MECHANISMS OF MANAGEMENT INTELLECTUAL PROPERTY OF HIGH TECHNOLOGY COMPANIES IN THE CONDITIONS OPEN INNOVATION - Y. Lebedeva (Вестник университета)
The article suggests the system of management intellectual property for high technology companies. Mechanisms of interaction of high technology companies with the subjects of the environment on the distribution of intellectual property rights within the framework of the implementation of joint innovation projects.